The Correct Rules for Facades Stone Lining - Ali Hussein Khudhair (Journal of Madenat Alelem University College, 2018)
The aim of this research is directed to investigate the local and national process of stone lining for building facades to determine the drawbacks associated with local implementation of stone lining compared with national one ; and to suggest rules to overcome existing drawbacks resulting meanly ; from the absence of clear rules for lining and lack of standard stone lining supports in addition to failure of existing non standard support due to action of corrosion resulting in dangerous collapse of stone lining .In this research, implementation rules , support means act as part of the structure and water proofing are suggested